Effects of Polysaccharides from Platycodon grandiflorum on Immunity-Enhancing Activity In Vitro - Xiaona Zhao; Yuge Wang; Peng Yan; Guodong Cheng; Cheng Wang; Na Geng; Xuepeng Wang; Jianzhu Liu (Molecules, 2017)
The study is aimed at investigating the immunoenhancement activity of polysaccharides from Platycodon grandiflorum polysaccharides (PGPSs) in vitro. In this study, some research on lymphocyte proliferation, cell cycle, and the levels of CD4+ and CD8+ T cells were performed. Four different concentrations of PGPSs (PGPStc, PGPS60c, PGPS80c, and PGPStp) were harvested and added to peripheral blood T lymphocytes. We observed significant increases in T lymphocyte proliferation at PGPStc groups individually or synergistically with phytohemagglutinin (PHA) at most concentrations, and their lymphocyte proliferation rates were the highest. The active sites of PGPStc and PGPS60c were subsequently chosen. Then, we utilized flow cytometry to determine lymphocyte cell cycle distribution and levels of CD4+ and CD8+ T cells. At most time points, PGPStc could facilitate lymphocyte cell cycle progression from the G0/G1 phase to the S and G2/M phases and, simultaneously, increase the levels of CD4+ and CD8+ T cells. These results indicate that PGPStc enhances the immune functions, suggesting that PGPStc could be a potential immunopotentiator for further in vivo and clinical trial experiments.